Work ability index of young employees and their sickness absence during the following year - Kujala, Veikko; Tammelin, Tuija; Remes, Jouko; Vammavaara, Elina; Ek, Ellen; Laitinen, Jaana (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'The work ability index is widely used in occupational health care. The aim of this study was to determine the extent to which a low index among young employees is predictive of sickness absence during the following year. ' ' METHODS ': 'Altogether 3725 employees aged 31 years were followed from 1997 to 1999 as part of the northern Finland birth cohort 1966 study. The participants’ self-administered questionnaires at baseline and a 1-year follow-up period with comprehensive sickness absence records was obtained from the Social Insurance Institution of Finland. The records contained only medically certified long-term sickness absences (>9 days). A multivariable logistic regression was used to examine how the work ability index and covariates were associated with sickness absence during the following year. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated for the index and its covariates. ' ' RESULTS ': 'In a comparison with an excellent index score (>44 points), a low score (<37 points) was associated with sickness absence for both the men (OR 3.6, 95% CI 1.6-7.9) and the women (OR 6.2, 95% CI 2.9 to 13.5) after adjustment for occupation, control over work, social support at work, marital status, number of children at home, physical activity, body mass index, and alcohol consumption. Of the 518 participants with a low index, 90 had long-term sickness absence, giving a positive predictive value of 17.4% (95% CI 14.1–20.6). The negative predictive value was 93.1% (95% CI 92.3–94.0). ' ' CONCLUSIONS ': 'For young employees, the work ability index is a practical tool for predicting long-term sickness absence, but it does not predict “no sickness absence”.
Keywords: classification of occupations; control over work; longitudinal study; number of children; occupational health; physical activity; prospective population-based study; questionnaire; sex factor; sickness absence; smoking; work ability index; young employee